ASSESSING THE MANIFESTATION OF CRITICAL THINKING IN ACADEMIC SPEAKING AMONG EFL UNIVERSITY STUDENTS: A STUDY OF CURRENT PRACTICES IN THE AI ERA - EL-Asri, Samira (English Education Department of STKIP Pasundan, 2026)
In an era marked by an unprecedent advancement of digital technologies, cultivating critical thinking as a core soft skill among students remain a persistent challenge, and does its assessment. In this regard, this study explores the current and most common practices used by university professors to assess EFL students’ manifestation of critical thinking in speaking in order to evaluate and adjust them according to the present context. Using a concurrent mixed-methods research design, the study recruited a sample of 364 EFL university students belonging to the same Department of English to collect quantitative data. Then, 18 of them were invited to take part in semi-structured interviews. The findings of the study revealed that the predominant type of examination students were generally accustomed to is the formal written exam. The findings also confirmed that most of the exams students previously had, both oral and written, put more focus on retention and memorization on the expense of inquisitiveness and examination of students’ higher order thinking cognitive abilities. Evidence from this study demonstrates the need for adopting and integrating alternative practices that target the assessment of critical thinking in speaking within EFL contexts and higher education as a whole.